Developing the Next Generation of Physicians. (21st November 2018) - LaRochelle, Jeffrey; Durning, Steven J; Gilliland, William; Henry, Jamie; Ottolini, Martin; Reamy, Brian; Ritter, Joan; Dorrance, Kevin A
Abstract: To improve health care, the USA needs to create a longitudinal medical education system that will develop physicians able to lead the transformation of health care toward a focus on the promotion of healthy behaviors aimed at preventing disease. The development of patient-centered care has been an important step in promoting healthy behaviors. However, to truly develop a meaningful relationship with a patient, a physician must first see them as a person, not as a list of diseases. Medical education should develop physicians able to provide person -centered care – moving beyond patient-centered care to focus more broadly on the entirety of the person, for whom being a patient is merely one aspect of their personhood. Restructuring medical education begins with the admission process itself, followed by longitudinal changes at the undergraduate, graduate, and continuing professional development levels that will reinforce the attributes critical for future physicians. The authors view this longitudinal approach through the theoretical framework of situated cognition, exploring personal, environmental, and social factors leading to success; outline several key stages of medical education from matriculation through continuing professional development; and identify potential areas that merit longitudinal efforts to develop future physicians able to promote positive health behaviors.